Family support on motivation of compliance and chemotherapy protocol among patients with breast cancer - Ulfah Nuraini Karim; Agung Setiyadi; Yeni Efrida (Universitas Muhammadiyah Magelang, 2023)
Chemotherapy is a therapy using drugs to kill cancer cells that have spread beyond the breast and axillary areas that cannot be seen or found. This study aimed to determine the relationship between family support and motivation to comply with chemotherapy protocols in breast cancer patients in Tarakan Hospital Jakarta. This type of research is descriptive and correlative with a cross-sectional approach with the simple random sampling technique of 73 respondents—the results of the research data analysis using the Chi-Square test. From the study's results, it can be concluded that there is a significant relationship between family support and motivation to comply with chemotherapy protocols in breast cancer patients. Therefore, family support is needed to improve the quality of life in breast cancer patients undergoing chemotherapy. Keywords: Chemotherapy; breast cancer; nursing care; nursing collaboration; family support